23.6%-efficient monolithic perovskite/silicon tandem solar cells with improved stability - Bush, Kevin A.; Palmstrom, Axel F.; Yu, Zhengshan J.; Boccard, Mathieu; Cheacharoen, Rongrong; Mailoa, Jonathan P.; Mcmeekin, David P.; Hoye, Robert L. Z.; Bailie, Colin D.; Leijtens, Tomas; Peters, Ian Marius; Minichetti, Maxmillian C.; et al. (Nature Energy, 2017)
As the record single-junction efficiencies of perovskite solar cells now rival those of copper indium gallium selenide, cadmium telluride and multicrystalline silicon, they are becoming increasingly attractive for use in tandem solar cells due to their wide, tunable bandgap and solution processability. Previously, perovskite/silicon tandems were limited by significant parasitic absorption and poor environmental stability. Here, we improve the efficiency of monolithic, two-terminal, 1-cm2 perovskite/silicon tandems to 23.6% by combining an infrared-tuned silicon heterojunction bottom cell with the recently developed caesium formamidinium lead halide perovskite. This more-stable perovskite tolerates deposition of a tin oxide buffer layer via atomic layer deposition that prevents shunts, has negligible parasitic absorption, and allows for the sputter deposition of a transparent top electrode. Furthermore, the window layer doubles as a diffusion barrier, increasing the thermal and environmental stability to enable perovskite devices that withstand a 1,000-hour damp heat test at 85 °C and 85% relative humidity.
CRIS-Team Scopus Importer:2022-06-05